The prevalence of tuberculosis and malaria in minority indigenous populations of South- East Asia and the Western Pacific Region: a systematic review and meta-analysis. (19th May 2022) - Gilmour, Beth; Alene, Kefyalew Addis; Clements, Archie
ABSTRACT: Infectious diseases have been shown to disproportionately affect indigenous populations. Tuberculosis (TB) and malaria continue to impose a significant burden on humanity and are among the infectious diseases targeted within the 2030 Agenda for Sustainable Development. A systematic review and meta-analyses were undertaken to evaluate the prevalence of TB and malaria infections within minority indigenous populations of the South-East Asia and Western Pacific Regions. The review was undertaken in accordance with The Preferred Reporting Items for Systematic Review and Meta-Analyses guidelines following a published protocol. A random effects meta-analysis was used to calculate the pooled prevalence of TB and malaria. A meta-regression analysis was applied to quantify associations with study covariates and a sub-group analysis undertaken where studies provided comparative data between minority indigenous and other population groups. From the 3, 275 unique publications identified, 24 on TB, and 39 on malaria were included in the final analysis. The pooled prevalence of TB was 2.3% (95% CI: 1.7, 2.9) and the pooled prevalence of malaria was 19.9% (95% CI: 15.9, 24.2). There was significant ( p = 0.000) heterogeneity (I 2 ) between studies. Significant difference was not observed in TB and malaria prevalence between minority indigenous and other population groups, although the odds ratio of malaria infection in minority indigenous populations was 1.15 (95% CI 0.99, 1.34: p -value 0.06) compared to other population groups. The review identified a paucity of data on TB and malaria in minority indigenous populations despite the significant prevalence and burden of these diseases within these regions.